Risk Management and Patient Safety; The National Safety and Quality Health Service (NSQHS) Standards - Juma, Aisha; Nazik, Suleiman (Global Journal of Health Sciences, 2025)
Purpose: The research aims at modifying two Standards of the National Safety and Quality Health Service (NSQHS) framework for UAE healthcare institutions which include both Clinical Governance and Medication Safety standards. This adaptation process is crucial for linking these standards to UAE regulations and healthcare infrastructure because of substantial cultural as well as legal technological and organizational differences between Australia and the UAE. Healthcare facilities in UAE will receive upgraded patient safety and quality of care through standards adaptations which reflect their specific operational needs. Methodology: The analysis methodically evaluates healthcare systems in Australia and UAE by involving their governance structures along with their combination of diverse cultures and system capabilities. A structured framework development method guides standard alignment with the UAE’s regulatory framework and adds suitable leadership strategies for diverse patient populations. The study delves into technology adoption mainly through artificial intelligence (AI) and digital health tools which enhance clinical decision-making ability and patient information retrieval. This analysis determines the implementation feasibility of electronic prescribing and medication tracking frameworks which will support the Medication Safety Standard within the UAE context due to its advanced technology infrastructure. Findings: A comprehensive governance framework requires development in order to achieve compatibility between the Clinical Governance Standard and UAE healthcare framework standards and employee population diversity. A combination of healthcare analytics with AI capabilities leads to substantial improvements in governance decision processes and patient care programs and quality assessment activities. The standard needs effective solutions to address regulatory matching requirements and cultural adaptation needs in order to function properly. Tests show that implementing electronic prescribing systems with nation-wide medication reconciliation programs will improve provider accountability and healthcare professional communication while decreasing medication errors. Adequate technology infrastructure within the UAE promotes these initiatives though the healthcare systems experiences impedance because of technical inconsistencies and regulatory barriers across regions. Unique Contribution to Theory, Practice and Policy: The UAE requires the development of a specific Clinical Governance Framework to fulfill legal requirements and address multicultural patient needs in the nation. Healthcare institutions must use AI and digital health technology to create data-driven decisions and enhance governance operation and quality assessment systems. It is crucial to establish nation-wide medication reconciliation standards across all healthcare facilities so care management remains consistent while minimizing medication errors in the UAE. The adoption of electronic prescribing systems and medication tracking platforms will boost healthcare provider communication by advancing patient protection measures. More research needs to be performed about AI and machine learning integration to expand the range of NSQHS standards and their application in UAE healthcare facilities.